2022
DOI: 10.1177/08862605221116317
|View full text |Cite
|
Sign up to set email alerts
|

Digital Sexual Violence and Suicide Risk in a National Sample of Sexual Minority Adolescents

Abstract: This paper aimed to examine the association between digital sexual violence (threat to post or nonconsensual posting of sexually explicit media) and suicidal (ideation, planning, and attempt) and non-suicidal self-harm behavior. The data for the current analysis come from an online sample of sexual minority adolescents (aged 14–17) recruited from across the United States ( n = 970). Multivariate logistic regressions were used to examine the association between digital sexual violence with suicide (ideation, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…On the other hand, they are unaware of the security aspect of digital rape. Because they think a rape can only be done physically [54]. Furthermore, they are also unaware of the threat of extortion from the exchange of photos and personal data sent to strangers on the internet.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, they are unaware of the security aspect of digital rape. Because they think a rape can only be done physically [54]. Furthermore, they are also unaware of the threat of extortion from the exchange of photos and personal data sent to strangers on the internet.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SM report more barriers to receiving safe healthcare services and, as a result, are less likely to seek care (Tanner et al, 2014; Williams et al, 2021). This is particularly concerning given that SM are at increased risk for victimization from intimate partner violence (IPV), including T-IPV such as revenge porn and cyber harassment (Gámez-Guadix & Incera, 2021; Srivastava et al, 2022). In a study of SM youth conducted by Srivastava et al (2022), 16% of the sample reported that they had been threatened or had their sexually explicit media posted/shared without their consent, with over a third at the hands of an ex-intimate partner.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly concerning given that SM are at increased risk for victimization from intimate partner violence (IPV), including T-IPV such as revenge porn and cyber harassment (Gámez-Guadix & Incera, 2021; Srivastava et al, 2022). In a study of SM youth conducted by Srivastava et al (2022), 16% of the sample reported that they had been threatened or had their sexually explicit media posted/shared without their consent, with over a third at the hands of an ex-intimate partner. The experience of online sexual victimization has been linked to poor mental health outcomes, including increased risk for self-harm, suicidal ideation, and suicide attempt (Gámez-Guadix & Incera, 2021; Srivastava et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One prominent concern is linked to the idea that people online are not always who they seem (i.e., catfishing), which can lead to physical and/or emotional harm (Freed et al, 2023; Jozsa et al, 2021). Online relationships may also lead to multiple forms of cyber dating abuse, such as digital sexual violence, emotional abuse, and harassment (Caridade et al, 2019; Hellevik, 2019; Srivastava et al, 2023). These harms and drawbacks can be heightened for those with minoritized identities, including lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth (Coyne et al, 2023; Ma et al, 2022) who tend to lack the knowledge and skills needed to navigate online dating spaces (Dhoest, 2022; Jozsa et al, 2021; Owens et al, 2023).…”
mentioning
confidence: 99%